Isolated small bowel transplantation outcomes and the impact of immunosuppressants: Experience of a single transplant center - Hilmi, Ibtesam A (Baishideng Publishing Group Co., Limited, 2013)
AIM: To investigate patient and graft outcomes in isolated small bowel transplant (SBTx) recipients and immunosuppressant induction agent impact on outcomes. METHODS: A retrospective review of the perioperative data of patients who underwent SBTx transplant during an 8-year period was conducted. The intraoperative data were: patient demographics, etiology of short gut syndrome, hemodynamic parameters, coagulation profiles, intraoperative fluid and blood products transfused, and development of post-reperfusion. The postoperative data were: hospital/intensive care unit stays, duration of mechanical ventilation, postoperative incidence of acute kidney injury, and 1-year patient and graft outcomes. The effects of the three immunosuppressant induction agents (Zenapax, Thymoglobulin, Campath) on patient and graft outcomes were reviewed. RESULTS: During the 8-year period there were 77 patients; 1-year patient and graft survival were 95% and 86% respectively. Sixteen patients received Zenapax, 22 received Thymoglobulin, and 39 received Campath without effects on patient or graft survival (P = 0.90, P = 0.14, respectively). The use of different immune induction agents did not affect the incidence of rejection and infection during the first 90 postoperative days (P = 0.072, P = 0.29, respectively). The Zenapax group received more intraoperative fluid and blood products and were coagulopathic at the end of surgery. Zenapax and Thymoglobulin significantly increased serum creatinine at 48 h (P = 0.023) and 1 wk (P = 0.001) post-transplant, but none developed renal failure or required dialysis at the end of the first year. CONCLUSION: One-year patient and graft survival were 95% and 86%, respectively. The use of different immunosuppressant induction agents may affect the intraoperative course and short-term postoperative morbidities, but not 1-year patient and graft outcomes.